Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1155/2016/1713897
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Effect and Mechanism of Yisui Shengxue Granules in Thalassemia Patients with Mild, Moderate, or Severe Anemia

Abstract: Yisui Shengxue granules, which is a Chinese traditional medicine, can increase hemoglobin, red blood cells, and Ret of thalassemia patients with mild, moderate, and severe anemia and thus relieve clinical anemia symptoms. Studies on mechanism found that Yisui Shengxue granules can increase the proliferation ability of hematopoietic stem cells. Emodin promoted colony forming of hematopoietic stem cells. Yisui Shengxue granules can increase the activity of GSH-PX in bone marrow blood and decreased the severity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…Our study results supported previous studies that showing that CHMs are effective, safe, less toxic, and have few side effects in treating anemia and blood-related diseases ( Liu et al, 2006 ; Wu et al, 2006 ; Wang et al, 2008 ; Gao and Chong, 2012 ; Chu et al, 2014 ; Fleischer et al, 2016a ; Fleischer et al, 2016b ; Cheng et al, 2016 ; Fleischer et al, 2017 ; Chen et al, 2018 ; Fleischer et al, 2018 ; Sun et al, 2018 ; Zhu et al, 2018 ). Zhang et al reported that a complex Chinese medicine, Yisui Shengxue Granule (YSSXG) may increase the relative mRNA expression level of the gamma-globin gene in the human K562 myelogenous cells in vitro ( Zhang and Wu, 2008 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our study results supported previous studies that showing that CHMs are effective, safe, less toxic, and have few side effects in treating anemia and blood-related diseases ( Liu et al, 2006 ; Wu et al, 2006 ; Wang et al, 2008 ; Gao and Chong, 2012 ; Chu et al, 2014 ; Fleischer et al, 2016a ; Fleischer et al, 2016b ; Cheng et al, 2016 ; Fleischer et al, 2017 ; Chen et al, 2018 ; Fleischer et al, 2018 ; Sun et al, 2018 ; Zhu et al, 2018 ). Zhang et al reported that a complex Chinese medicine, Yisui Shengxue Granule (YSSXG) may increase the relative mRNA expression level of the gamma-globin gene in the human K562 myelogenous cells in vitro ( Zhang and Wu, 2008 ).…”
Section: Discussionsupporting
confidence: 92%
“…Chu et al reported that this YSSXG Chinese medicine may contribute to these patients with thalassemia via increasing the relative mRNA expression levels of globin genes and enhancing the antioxidant activities in erythrocytes ( Chu et al, 2014 ). Cheng et al, reported that YSSXG Chinese medicine may also increase proliferation of hematopoietic stem cells ( Cheng et al, 2016 ). While, Liu et al suggested that YSSXG Chinese medicine may have a protective effect against thalassemia via inhibiting the formation of alpha-globin-cytotoxic precipitates in erythrocytes by upregulating GATA-1 transcription factor and alpha-hemoglobin stabilizing protein (AHSP) ( Liu et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%